Polymorph screening and solubility characterization of lercanidipine hydrochloride - Repin, Ilia Alekseevich (2019)
The study of the polymorphism of lercanidipine hydrochloride (LRC) has revealed a significative impact on solubility with a strong dependence on buffer type, pH, and ionic strength. For the first time, unexpected changes in the solubility ratio between two polymorphic forms of LRC (forms I and II) depending on the media composition were identified, and its potential consequences to the pharmacokinetic performance were evaluated through physiologically based pharmacokinetic (PBPK) modeling using GastroPlus(TM); the results suggest that in cases of low stomach acidity, form II is potentially less bioavailable than form I. Phosphate buffer showed to promote less solubility variation in the concentration range of 0.01-0.1 mol·L-1 and favored solubility increase for both forms in the 2-3.5 pH range when compared to a citric acid buffer. Solid-state characterization of both polymorphs accompanied by polythermal solubility experiments carried out in ethanol and acetonitrile permitted to establish the thermodynamic relationship between the two polymorphs as monotropic. Furthermore, forced degradation was applied to determine thermal and photostability of each form, determining form I as the less chemically stable. Determination LRC form II crystalline structure was accomplished based on the successful obtainment of its single crystal, while structural data of LRC form I was estimated by applying single-value decomposition approach to its X-ray powder diffraction scans.